From Normal to Obesity and Back: The Associations between Mitochondrial DNA Copy Number, Gender, and Body Mass Index - Daria Skuratovskaia; Larisa Litvinova; Maria Vulf; Pavel Zatolokin; Konstantin Popadin; Ilia Mazunin (Cells, 2019)
Mitochondrial DNA (mtDNA) encodes core subunits of oxidative phosphorylation complexes and, as a result of intricate regulatory crosstalk between nuclear and mitochondrial genomes, the total number of mtDNA copies fits the requirements of each cell type. Deviations from the physiological number of mtDNA copies are expected to be deleterious and might cause some inherited diseases and normal ageing. We studied 46 obese patients with type 2 diabetes (T2DM) one year after a laparoscopic sleeve gastrectomy (LSG) and Roux-en-Y gastric bypass (RYGB). The results were compared with normal-weight patients without T2DM (control group 1) (body mass index (BMI) = 22.5 ± 3.01 kg/m2) and patients with obesity without T2DM (control group 2) (BMI = 36 ± 3.45 kg/m2). We detected an increase of mtDNA copy number in the cells of the buffy coat obtained from peripheral blood, sampled one year after bariatric surgery. We also found that average mtDNA copy number as well as its dynamics (before and after the surgery) are gender-specific. To the best of our knowledge, this is the first evidence for the restoration of mtDNA copy number in obese patients after LSG and RYGB.